ANALISIS KANDUNGAN HARA MAKRO DI DALAM TANAH DENGAN METODE NEAR INFRA RED (NIR) - Eka Nuryanto; Ellen Gouw (Pusat Penelitian Kelapa Sawit, 2017)
Fertilizer costs are the largest component of production costs in oil palm plantations. To obtain precise data dosage and type of fertilizer used, it is necessary to analyze the contents of macro and micronutrients in soil in oil palm plantation. Analysis of nutrients content using the conventional method is expensive and not environmentally friendly. Analysis by Near Infra Red (NIR) spectroscopyy method has several advantages such as rapid, does not require chemicals, and environmentally friendly. Soil samples used in this study were 419 samples originating from the farm of PT. Perkebunan Nusantara in North Sumatra. Nutrients contents of the soil was determined by conventional methods and is used for calibration and validation of NIR Master of Buchi. Results of soil nutrients analysis with NIR method showed that the 2 value of r for N, P, K, Mg, and Ca respectively is 0,08; 0,7; 0,5; 0,3; and 0,8. While the difference of value of analysis using conventional method and NIR for parameter N, P, K, Mg and Ca respectively is 0.012%, 8,317 ppm, 0.045 meq/100g, 0.173 meq/100g, and 2 0.936 meq/100g. Although the value of r is relatively low but the difference in the analysis results using conventional and NIR methods is also low . Thus the analysis of macro nutrient content in the soil in oil palm plantations is very possible can be done with NIR spectroscopy method.